Mind Healing Technique as Applied Tasawuf: Reframing Healing Through Islamic Transpersonal Consciousness: Mind Healing Technique sebagai Tasawuf Terapan: Membingkai Ulang Penyembuhan Melalui Kesadaran Transpersonal Islam - Ahmad Jais; Muhammad Haikal As-Shidqi (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2026)
his study aims to formulate Mind Healing Technique (MHT) of Indonesia as a transpersonal-sufistic model of consciousness-based healing. The study is motivated by the growing need for a holistic healing framework that does not reduce psychological suffering to clinical symptoms alone, but also considers existential meaning, spiritual disconnection, and the purification of the self. This research employs a qualitative-conceptual design through library research and thematic-conceptual analysis. The data were drawn from transpersonal psychology, consciousness studies, spiritually integrated psychotherapy, Islamic psychotherapy, and classical Sufi literature on fitrah, nafs, qalb, maqāmāt, and tazkiyat al-nafs. The findings show that MHT reframes healing as a transformation of consciousness from Ego–Amarah–Keinginan (E-A-K), which represents egoic reactivity, anger, and desire, toward Suci–Murni–Bijak–Tenang (S-M-B-T), which represents purified, reflective, wise, and serene awareness. This movement is interpreted as a contemporary operationalization of tazkiyat al-nafs and a return to fitrah through maqāmāt such as taubah, zuhud, sabr, tawakkal, and riḍā. The study implies that MHT may contribute to Sufi psychotherapy, Islamic counseling, and holistic mental health as a complementary psychospiritual framework. The originality of this article lies in its conceptual integration of transpersonal psychology and applied tasawuf through the E-A-K and S-M-B-T structure as a psychospiritual map of healing.